Managing construction disputes - Motsa, Caleb Dumisa (2006)
Construction projects are increasingly complex, resulting in complex contract documents. Complex construction can likewise result in complex disputes. Disputes is inevitable in construction projects which predominantly arise from complexity and magnitude of works, multiple prime contracting parties, poorly prepared and/ or executed contract documents, inadequate planning, financial issues and communication problems. Any of these factors can overturn a project and lead to complicated litigation, arbitration, mediation, time overrun, increased costs and a relationship break down among members of different parties involved. The objectives of this study are to identify the root causes of construction disputes as well as their impact on client’s organization. The methodology of study adopted was through questionnaire survey where the target respondents were clients, consultants and contractors. Based on the analyzed data, there are nine root causes of construction disputes caused by clients, five root causes caused by consultants and four root causes caused by contractors have been identified in the local construction industry. The impact of construction disputes in client’s organization as found in the study are time consuming, cost effective, loss of reputation and sour relationship between stakeholders and also loss of profit and business validity. ADRs were observed as the best method of resolving disputes because they were identified as none time consuming and cost effective. From the findings it can be concluded that construction disputes are a cause of concern in every project and the solution to this problem is to avoid and cautiously manage them for smooth running of construction process, prevention is believed is better than cure.